The Effect of Hypertension on Hearing Sense - A.C Romdhoni (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Hypertension is an important health problem because it has a high prevalence and can cause damage to target organs. The relationship between hypertension and hearing loss is not difficult to understand, when blood pressure becomes high blood vessel damage occurs. Hearing loss cases caused by hypertension are considerable, in America 64 million people aged 18 to 75 years suffer from hypertension, 40% with hearing loss. This damage is not centered on one area of the body, but the whole body is also affected, including the ears. The incidence of hearing loss in hypertension is due to the occurrence of inner ear damage due to high pressure in the vascular system, changes in microcirculation and the occurrence of ionic changes.